Analysis of mutations in tumor and normal adjacent tissue via fluorescence detection. (28th December 2020) - Kay, Jennifer E.; Mirabal, Sheyla; Briley, William E.; Kimoto, Takafumi; Poutahidis, Theofilos; Ragan, Timothy; So, Peter T.; Wadduwage, Dushan N.; Erdman, Susan E.; Engelward, Bevin P.
Abstract: Inflammation is a major risk factor for many types of cancer, including colorectal. There are two fundamentally different mechanisms by which inflammation can contribute to carcinogenesis. First, reactive oxygen and nitrogen species (RONS) can damage DNA to cause mutations that initiate cancer. Second, inflammatory cytokines and chemokines promote proliferation, migration, and invasion. Although it is known that inflammation‐associated RONS can be mutagenic, the extent to which they induce mutations in intestinal stem cells has been little explored. Furthermore, it is now widely accepted that cancer is caused by successive rounds of clonal expansion with associated de novo mutations that further promote tumor development. As such, we aimed to understand the extent to which inflammation promotes clonal expansion in normal and tumor tissue. Using an engineered mouse model that is prone to cancer and within which mutant cells fluoresce, here we have explored the impact of inflammation on de novo mutagenesis and clonal expansion in normal and tumor tissue. While inflammation is strongly associated with susceptibility to cancer and a concomitant increase in the overall proportion of mutant cells in the tissue, we did not observe an increase in mutations in normal adjacent tissue. These results are consistent with opportunities for de novo mutations and clonal expansion during tumor growth, and they suggest protective mechanisms that suppress the risk of inflammation‐induced accumulation of mutant cells in normal tissue.